Transcriptome analysis of human brain tissue identifies reduced expression of complement complex C1Q Genes in Rett syndrome. (December 2016) - Lin, Peijie; Nicholls, Laura; Assareh, Hassan; Fang, Zhiming; Amos, Timothy; Edwards, Richard; Assareh, Amelia; Voineagu, Irina
Abstract Background MECP2, the gene mutated in the majority of Rett syndrome cases, is a transcriptional regulator that can activate or repress transcription. Although the transcription regulatory function of MECP2 has been known for over a decade, it remains unclear how transcriptional dysregulation leads to the neurodevelopmental disorder. Notably, little convergence was previously observed between the genes abnormally expressed in the brain of Rett syndrome mouse models and those identified in human studies. Methods Here we carried out a comprehensive transcriptome analysis of human brain tissue from Rett syndrome brain using both RNA-seq and microarrays. Results We identified over two hundred differentially expressed genes, and identified the complement C1Q complex genes (C1QA, C1QB and C1QC) as a point of convergence between gene expression changes in human and mouse Rett syndrome brain. Conclusions The results of our study support a role for alterations in the expression level of C1Q complex genes in RTT pathogenesis.